2022
DOI: 10.3390/jcm11113043
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride and Glucose Index as a Screening Tool for Nonalcoholic Liver Disease in Patients with Metabolic Syndrome

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is regarded as a component of metabolic syndrome, which involves insulin resistance (IR) as the primary physiopathological event. The aim of this study was to establish the association between IR, assessed using the triglyceride and glucose index (TyG), and histopathological features of NAFLD lesions. Methods: The study included 113 patients with metabolic syndrome. Fasting plasma glucose (FPG), fasting lipid profiles and liver enzymes were measured. IR was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Triglyceride glucose index (TyG), which is calculated from fasting glucose and triglycerides, has been regarded as an inexpensive surrogate of insulin resistance (IR) in the setting of clinical practice, and even shows better performance compared with the traditional homeostasis model (HOMA-IR) in evaluating IR [3,4]. Accumulated evidence has revealed that the TyG index is closely related to cardiovascular diseases, including carotid atherosclerosis, metabolic syndrome, subclinical atherosclerosis, and coronary artery calcification [5][6][7][8]. Furthermore, an increased TyG index not only is associated with the incidence of atherosclerotic disease but also can predict adverse outcomes in patients with established CAD [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Triglyceride glucose index (TyG), which is calculated from fasting glucose and triglycerides, has been regarded as an inexpensive surrogate of insulin resistance (IR) in the setting of clinical practice, and even shows better performance compared with the traditional homeostasis model (HOMA-IR) in evaluating IR [3,4]. Accumulated evidence has revealed that the TyG index is closely related to cardiovascular diseases, including carotid atherosclerosis, metabolic syndrome, subclinical atherosclerosis, and coronary artery calcification [5][6][7][8]. Furthermore, an increased TyG index not only is associated with the incidence of atherosclerotic disease but also can predict adverse outcomes in patients with established CAD [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Another study published in 2022, analyzing NAFLD defined by liver biopsy in patients with metabolic syndrome, reported a total frequency of liver steatosis of 92.03%, ranging from 71.43% in patients with metabolic syndrome who had a normal weight to 91.84% in overweight patients, to 100% in patients with obesity [ 40 ]. Interestingly, in our research, anthropometric parameters were associated with MAFLD only in females.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, triglyceride accumulation, as a hallmark of NAFLD, may be one predictor of the development of NAFLD in later life [13,14]. In response to hepatocellular damage, there is a proportional release of ALT into the circulation, which is thought to be a sensitive marker of liver injury and disease progression.…”
Section: Discussionmentioning
confidence: 99%